Antecedents of work design in the context of entrepreneurship - Ward, M.K.; Parker, Sharon; Hay, Georgia (2019)
Entrepreneurs face continual challenges of extremely demanding, stressful, complex, and dynamic work (e.g., de Mol, Ho & Pollack, 2018). As founders grow their start-ups, they re-design existing jobs and create new roles. In essence, entrepreneurs are designing future work. Surprisingly few papers have integrated work design with entrepreneurship, leaving entrepreneurs to design work for themselves and others without drawing from the knowledge of over 100 years of work design research (Parker, Morgeson, & Johns, 2017). Investigating work design in entrepreneurship holds promise to benefit both fields (Baron, 2010). First, work design can offer insights into ways of designing work in start-ups so that demands can be met while maintaining well-being, motivation, and fostering employee development (Parker, 2014). Second, work design can use the entrepreneurial context to refine and build on existing theories. Start-ups offer a context to conduct valuable multi-level studies. For example, initial evidence shows that the way founders view their work roles impacts how they influence their work design, the work design of their employees, and the performance of their start-up (Mathias & Williams, 2018). Fourth, an increasing proportion of the workforce are becoming entrepreneurs. Therefore, work design scholars could offer valuable insights if we begin building theories that apply to the often extreme work context of start-ups. Study goals and Relevance: Extending work by Parker, Van den Broeck & Holman (2017), the goal of this paper is to develop a theoretical framework that models individual characteristics of entrepreneurs and contextual variables as key antecedents to work design. The main research question is: what are the important antecedents to shifts in work design as start-ups grow? Method: Interview and observational data will be collected in a qualitative study. Data will be analysed using a grounded theory approach modelled after Huang (2018). There are no results yet to report. Discussion: If work design wants to remain relevant to work as jobs are increasingly incorporating automation, then we must be part of the conversation with entrepreneurs. They are building companies and shaping future work in their startups. We must build an understanding of work design in startups in order to make recommendations and subsequently improve future work.